Inhibitory effect of resveratrol on the pharmacokinetic of ibrutinib by UPLC–MS/MS. (2nd January 2019) - Wen, Jian; Bao, Su-Su; Zhang, Bo-Wen; Liu, Teng-Hui; Ou-Yang, Qiu-Geng; Cai, Jian-Ping; Zhou, Hong-Yu
Abstract: Objective: To investigate the impact of resveratrol on the metabolism of ibrutinib in vitro and in vivo . Methods: In vitro, rat liver microsomes (RLM) and human liver microsomes (HLM) were used to study. In vivo, 18 male SD rats were randomly divided into three groups ( n  = 6): ibrutinib and the multiple dose of 100 mg/kg resveratrol for consecutive 7 days (Group A), ibrutinib and the single dose of 100 mg/kg resveratrol (Group B), ibrutinib (Group C). Processed samples were analyzed by UPLC–MS/MS. Results: Resveratrol showed inhibition on RLM and HLM in vitro . The IC50 of resveratrol was 8.745 µM in RLM and 7.789 µM in HLM. Furthermore, Groups A and B both increased the AUC and reduced the CLz/ F . The C max of Group A and the MRT(0– t ) of Group B were significantly improved. Conclusions: Resveratrol inhibits the pharmacokinetic of ibrutinib in vitro and in vivo . It is necessary to pay more attention to adjust the dose of the drug when resveratrol is used in combination with ibrutinib.